2009
DOI: 10.1016/j.leaqua.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A framework for examining leadership in extreme contexts

Abstract: a r t i c l e i n f o a b s t r a c tIn this review, we develop a framework to guide future research and to examine the execution of leadership in extreme contexts. We start by defining and distinguishing extreme contexts from crisis and other contexts. A five component typology is developed comprised of magnitude of consequences, form of threat, probability of consequences, location in time and physical or psychological-social proximity. We discuss the unique influences these components have on leadership pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
555
2
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(588 citation statements)
references
References 158 publications
(188 reference statements)
16
555
2
15
Order By: Relevance
“…In the transition phase a series of planning and preparation processes help members of the MTS develop shared mental models about how individuals and teams are supposed to think and interact during the course of an operation. Such processes (e.g., Safe Job Analyses, Tool Box Meetings, and Task Plans) help members of the MTS to see the big picture of the operation, reinforce standard operating procedures, anticipate problems, and minimize their occurrence 5 . However, given the complex nature of the work and the dynamic environment in which it takes place unexpected events will occur and the system must be able to respond quickly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the transition phase a series of planning and preparation processes help members of the MTS develop shared mental models about how individuals and teams are supposed to think and interact during the course of an operation. Such processes (e.g., Safe Job Analyses, Tool Box Meetings, and Task Plans) help members of the MTS to see the big picture of the operation, reinforce standard operating procedures, anticipate problems, and minimize their occurrence 5 . However, given the complex nature of the work and the dynamic environment in which it takes place unexpected events will occur and the system must be able to respond quickly.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental context is potentially extreme. Hannah et al [5] define an extreme context as one "where one or more extreme events are occurring or are likely to occur that may exceed the organization's capacity to prevent and result in an extensive and intolerable magnitude of physical, psychological, or material consequences to-or in close physical or psycho-social proximity to-organization members." An IMR trip involves many potential risks for the crew, vessel (e.g.…”
Section: The Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that where there is minimal cultural distance between home and host cultures there should be less culture shock and greater ability of expatriates to understand the attitude and actions of local people or to predict behavior of local people (Gudykunst & Hammer, 1988). Fisher and Hutchings (2013) suggested that context matters and that cultural distance takes on more significance in an extreme context when there is threat of injury and to life and events occur which are unplanned (Hannah, Uhl-Bien, Avolio, & Cavarretta, 2009) and stress is more pronounced (for a discussion of stress and culture shock see also Redmond, 2000).…”
Section: Cultural Distancementioning
confidence: 99%
“…Leadership and trust are two relevant elements to explain the difference in performance between organizations that are often similar (Braun et al, 2013;Pinheiro Neto, 2013;Zanini et al, 2003;Haas, 2005; Legood, Thomas and Sacramento, 2016;Hasel and Grover, 2017). Especially in contexts of high complexity and unpredictability, engagement and trust are essential to ensure cooperation in the search for internal adjustments necessary to construct rapid responses to the challenges of the environment (Hannah et al, 2009).…”
Section: Introductionmentioning
confidence: 99%